How do digital competencies promote entrepreneurial intention among vocational students? A mediation analysis of entrepreneurial self-efficacy and entrepreneurial mindset - Any Sutiadiningsih; Ila H.P. Dewi; Wahyu Ratnasari; Achmad Taufiq; Mauren Gita Miranti (Cogent Education)
The increasingly rapid development of technology has encouraged entrepreneurs to utilize digital technology in their new business scope. So, it is essential to strengthen digital competency from the start of studying at school to college for vocational students. Many studies highlight the critical role of digital competency in entrepreneurial intentions. However, more studies are still needed to discuss digital competency’s role in entrepreneurial intentions by involving vocational students’ entrepreneurial mindset and entrepreneurial self-efficacy. This study investigates the influence of digital competence, entrepreneurial mindset, and entrepreneurial self-efficacy on vocational students’ entrepreneurial intentions. We use structural equation modeling to test the causal relationship. There were 250 students at vocational colleges in Surabaya East Java involved in this study. This research is survey research. The study results concluded that digital competency did not directly influence vocational students’ entrepreneurial intentions. Meanwhile, entrepreneurial intentions are directly influenced by entrepreneurial mindset and entrepreneurial self-efficacy. Additionally, we found that digital competency plays a role in predicting entrepreneurial intentions, but only if mediation involves entrepreneurial mindset and entrepreneurial self-efficacy. The findings of this study provide important implications for educational practitioners in developing various programs that support strengthening vocational students’ entrepreneurial intentions.